THE PROFILE AND CLINICAL EVIDENCE OF EFFECTIVENESS OF OLAPARIB IN TRIPLENEGATIVE BREAST CANCER: A REVIEW - Faathiansyah, Muhammad Reza Al (Ridwan Institute, 2024)
Triple-negative breast cancer (TNBC) is one of the most common malignancies in women. The majority of patients with TNBC have a poor prognosis. The main objective of this study is to review the profile and clinical evidence of the effectiveness of Olaparib in treating TNBC. A literature search was conducted using multiple electronic databases, including PubMed, Google Scholar, JSTOR, and Scopus. The search was focused on articles published up to June 2024, ensuring the inclusion of the latest and relevant studies. The primary objective was to investigate the mechanism of action, toxicity profile, resistance mechanisms, and therapeutic effectiveness of olaparib in the treatment of TNBC, regardless of their prior chemotherapy treatment for metastatic breast cancer, prior platinum-based chemotherapy, or usage of cyclin-dependent kinase 4/6 inhibitors (Balmana et al., 2022). The results of this research suggest that the pharmacological efficacy and safety characteristics of this medication in TNBC patients are similar to those reported in the OlympiAD study. Furthermore, stratification of patients for this medication is possible due to the diagnostic techniques that can predict the presence of the BRCA mutation in order to optimize its efficacies. Additionally, developing and validating new biomarkers beyond BRCA mutations for patient stratification could optimize targeted therapy approaches.